High-Sensitivity Large-Area Photodiode Read-Out Using a Divide-and-Conquer Technique - Guillermo Royo; Carlos Sánchez-Azqueta; Concepción Aldea; Santiago Celma (Sensors, 2020)
In this letter, we present a novel technique to increase the sensitivity of optical read-out with large integrated photodiodes (PD). It consists of manufacturing the PD in several pieces, instead of a single device, and connecting a dedicated transimpedance amplifier (TIA) to each of these pieces. The output signals of the TIAs are combined, achieving a higher signal-to-noise ratio than with the traditional approach. This work shows a remarkable improvement in the sensitivity and transimpedance without the need for additional modifications or compensation techniques. As a result, an increase in sensitivity of 7.9 dBm and transimpedance of 8.7 dBΩ for the same bandwidth is achieved when dividing the photodiode read-out into 16 parallel paths. The proposed divide-and-conquer technique can be applied to any TIA design, and it is also independent of the core amplifier structure and fabrication process, which means it is compatible with every technology allowing the integration of PDs.